Construction of The E-Government Case Study of Japan and Estonia - Nozomi Tomura; Saki Uehara; Konosuke Kaneta; Ryosuke Hara; Ryogo Sasaki; Maho Tsuchida; Ayu Shibuya; Maiko Yamashita (Bright Institute, 2021)
The internet and PCs have been spreading in the world since the 1990s. The usage of these technologies not only in the business field but also in ordinary society. One of those business styles is Electronic Commerce. Most of the governments of countries and economists are taking these information technologies into their policies and developing them as their own IT policy. Above all, This paper summarized the history, structure, concrete outcomes and future plans for ICT, which is being advanced in Estonia, many of the ICT society including Japan is eager to realize, and introduces items that should be adopted to Japan.